Exposure to Low Doses of Oxybenzone During Perinatal Development Alters Mammary Gland Stroma in Female Mice - Matouskova, Klara; Bugos, Jennifer; Schneider, Sallie S.; Vandenberg, Laura N. (Frontiers in Toxicology, 2022)
Mammary stroma is a prominent modulator of epithelial development, and a complex set of interactions between these tissue compartments is essential for normal development, and can be either permissive or restrictive in tumor initiation and progression. During perinatal development, exposures of mice to oxybenzone, a common UV filter, environmental pollutant and endocrine disruptor, induce alterations in mammary epithelium. Our prior research indicates that oxybenzone alters mammary epithelial structures at puberty and in adulthood. We had also previously observed changes in the expression of hormone receptors at puberty (e.g., oxybenzone induced a decrease in the number of epithelial cells positive for progesterone receptor) and in adulthood (e.g., oxybenzone induced a decrease in the number of estrogen receptor-positive epithelial cells), and increased body weight in adulthood. Here, we investigated mammary stromal changes in BALB/c animals exposed during gestation and perinatal development to 0, 30, or 3000 μg oxybenzone/kg/day. In mice exposed to 30 µg/kg/day, we observed morphological changes in adulthood (e.g., a thicker periductal stroma and adipocytes that were considerably larger). We also observed an increased number of mast cells in the mammary stroma at puberty which may represent a transient influence of oxybenzone exposure. These results provide additional evidence that even low doses of oxybenzone can disrupt hormone sensitive outcomes in the mammary gland when exposures occur during critical windows of development, and some of these effects manifest in later life.